ANALYSIS OF QUEUE THEORY AND SERVICE OPTIMIZATION IN THE DRIVE THROUGH SYSTEM OF MCDONALD'S S. PARMAN, SAMARINDA BRANCH USING THE SINGLE SERVER SYSTEM MODEL - Ambarita, Nita Priska (VARIABLE RESEARCH JOURNAL, 2025)
McDonald's is a multinational fast food company originating from the United States that implements a drive-thru system at some of their outlets. The purpose of this study is to see how optimal the service is at McDonald's drive thru S Parman Samarinda branch. McDonald's drive thru S Parman Samarinda branch uses a single server queue system. The results of this study show that a single server system is very appropriate to use because customers can be served well and get optimal time. If the arrival rate (λ) is 8 customers per hour and the service rate (μ) is 12 customers per hour, then the system is stable because λ < μ. This can be seen from the number of individuals or customers waiting in the queue (Lq), which amounted to 1.33. The average number of customers in the system (L) is a total of 2. The probability of the absence of an empty buyer or server (P0) is 33%.